PATHOLOGICAL ASPECTS OF SEED-BORNE MYCOFLORA OF PINUS CARIBAEA MORELET VAR. HONDURENSIS (1990)
A survey of, the mycoflora of three seed lots of Pinus caribaea var. hondurensis was carried out using the incubation tests for the detection of seed-borne fungi on agricultural seeds. The seed-borne fungi identified were: Acromonium sp., Aspergillus flavus, A. fumigatus, A. niger, A. tamarii, Botrytis sp., Botryodiplodia theobromae, Chaetomium funicola, C. globosum, C. indicum, Cladosporium oxysporum, Dendrophoma sp., Fusarium eqruiseti, F. moniliforme var. intermedium, Gliocladium roseum, Macrophoma spp., Mucor spp., paecilomyces variotii, Penicillium citrinum, P. cyclopium, Pestalotiopsis spp., Phialophora fastigiata, Phomopsis occulta., Rhizopus sp. and Trichoderma sp. Seed-debris (pieces of cones and twigs) and stones also carried a large proportion of these pathogenic and saprophytic fungi. Using scanning electron microscope, no propagules of obligate parasitic pathogens were seen on the seed coat but spores and mycelia of some facultative pathogens were observed. Most of the seed-borne fungi were carried externally on the testa. Pinus caribaea var. hondurensis seeds inoculated with spore suspension and mycelial discs of the following fungi: Aspergillus niger, Fusarium moniliforme var. intermedium and F. eguiseti had drastic reduction in germination. F. moniliforme var. intermedium and F. eguiseti caused wilting and sudden death (damping-off) in 3 week and 3 month-old inoculated seedlings (20-60% mortality) 7 days after inoculation. Inoculated stems showed disintegration of cell-walls, parenchyma cells and fibres. Aspergillus niger had no effect on inoculated seedlings while Phialophora fastigiata had no effect on both the inoculated seeds and seedlings. Seeds which were surface sterilized for 5 minutes in 1% sodium hypochlorite and planted in autoclaved sterilized soil gave a germination percentage of 42 while seeds which were not surface sterilized but planted in sterilized soil gave 20%. Damping-off and wilting were observed in 10-12% of the seedlings which emerged from the two treatments 5-30 days after germination. Botryodiolodia theobromae, Fusarium moniliforme var. intermedium, Rhizoctonia spp. and Rhizopus spp. were isolated from the diseased seedlings. The effect of three fungicides: Benlate, Captan and Thiram in controlling the growth of the frequently occurring seed-borne fungi (Aspergillus niger. Fusarium moniliforme var. intermedium and Phialophora Fastigiata) was studied in vitro. Only Benlate at concentrations of 1 ppm and above inhibited the growth of the three fungi. Thiram inhibited the growth of Aspergillus niger and Phialophora fastigiata at 20 and 400 ppm respectively while Captan inhibited the growth of Aspergillus niger at 40 ppm.